The Clinico-Pathological Spectrum of Endometrial Lesions in Patients with Abnormal Uterine Bleeding in Accordance with PALM-COEIN Classification: A Prospective Study of 3 Years in a Tertiary Care Hospital of Western Uttar Pradesh - Khan, Roobina; Haiyat, Sadaf; Maheshwari, Veena; Hakim, Seema (Annals of Pathology and Laboratory Medicine, 2019)
Background: Abnormal uterine bleeding (AUB) is one of the most frequently encountered gynecological complaints in women associated with considerable morbidity and mortality. This study may help clinicians in our population to improve their therapeutic strategies by resorting to minimally invasive modalities and avoiding unnecessary hysterectomies. The aim of this study is to study the clinic-pathological spectrum and histological patterns various endometrial lesions in patients with AUB in accordance with PALM-COEIN classification. Methods: The present study was carried out on 265 patients over a period of 2 years in the Department of Pathology, Jawaharlal Nehru Medical College, A.M.U, Aligarh. Endometrial tissue was collected by dilatation and curettage (D and C) and endometrial biopsy and was sent to the histopathology laboratory for evaluation. Result: The most common clinical presentation was menorrhagia (43.4%), followed by metrorrhagia (19.3 %). Age of patients ranged from 15 to 70 years with peak incidence found in the 5th decade (41-50 years) (35.4%). On histopathological examination, non- structural causes accounted for the majority of the diagnosis (37%) in which normal cyclical endometrium (AUB-E) was the commonest lesion seen in 37.8 % of cases. Endometrial hyperplasia (AUB-M) was the most common histopathological diagnosis 84(31.7%) amongst structural causes in our study. This was followed by endometrial polyp (AUB-P) in 12(4.5%) cases and endometrial carcinoma in 4(1.5%) respectively. Conclusion: Our study revealed a clustering of cases around perimenopausal age group. Histopathological examination of endometrium is gold standard diagnostic tool in evaluation of AUB and there is an age specific association of endometrial lesions.